Self-help Therapy for Obsessive-compulsive Disorder - Pearcy, Caitlin Patricia (Curtin University, 2016)
The aim of this research was to investigate the use of self-help therapy for the treatment of Obsessive-compulsive disorder. Firstly, a meta-analytic study found that self-help therapy for OCD improved symptoms across varying levels of therapeutic contact. The second study strengthened the evidence surrounding the metacognitive model, finding significant relationships between OCD symptoms and metacognition. In the third and fourth studies, an online metacognitive program for OCD was developed and evaluated within a preliminary trial.